PENINGKATAN KAPASITAS PENGELOLAAN BADAN USAHA MILIK DESA (BUMDES) DI DESA KOKA DAN DESA KEMBES 2 KECAMATAN TOMBULU - Lumintang, Juliana; Waani, Fonny Jeane (Universitas Sam Ratulangi, 2020)
Bumdes in Koka and Kembes 2 villages have carried out activities with simple organizing and types of activities that did not go well. The initial capital of Bumdes was not developed and the types of activities were stagnant. The problem is, the management of the activities of Village-Owned Enterprises (Bumdes) in Koka and Kembes Dua Villages, has not run well in accordance with Bumdes management rules issued by the Minister of Villages and Disadvantaged Regions No. 4 of 2015, the business planning process and business feasibility analysis not done so that the selection of business types is done carelessly. The solution that has been implemented is to strengthen the management of the Bumdes to the Bumdes management and village officials so that the government and the Bumdes management will learn about the importance of correct Bumdes management by conducting business planning and business feasibility analysis. The method used is lecture and Focus Group Discusion (FGD) mapping of potential and Bumdes business type selection.